2018
DOI: 10.1016/j.cemconcomp.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methyl methacrylate) capsules as an alternative to the ‘’proof-of-concept’’ glass capsules used in self-healing concrete

Abstract: Development of suitable capsules is essential to achieve self-healing by encapsulation. In the context of self-healing concrete, capsules that can be easily mixed into concrete and release the healing agent when cracking occurs are ideally required. The optimization of these properties would allow for a successful implementation at large scale in practical (concrete) applications. In the present work, the suitability of polymeric cylindrical capsules made of poly(methyl methacrylate) (PMMA) to carry healing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…PMMA_2, PS, PLA and PMMA_1‐PEG capsules broke for very large cracks only. Subsequent real‐scale tests revealed that the resistance of cracked concrete against chloride could be increased for concrete with mixed‐in PMMA or glass capsules filled with water repellent agent . Glass capsules provided better crack sealing compared to PMMA capsules as a result of the more uniform distribution in the concrete beam, while the PMMA capsules tended to float.…”
Section: Encapsulated Autonomous Self‐healing (Polymers or Minerals)mentioning
confidence: 99%
“…PMMA_2, PS, PLA and PMMA_1‐PEG capsules broke for very large cracks only. Subsequent real‐scale tests revealed that the resistance of cracked concrete against chloride could be increased for concrete with mixed‐in PMMA or glass capsules filled with water repellent agent . Glass capsules provided better crack sealing compared to PMMA capsules as a result of the more uniform distribution in the concrete beam, while the PMMA capsules tended to float.…”
Section: Encapsulated Autonomous Self‐healing (Polymers or Minerals)mentioning
confidence: 99%
“…Since the survival of those external capsules during the vigorous mixing process and also, during casting procedures is critical for this capsule-based methodology, researchers also developed new evaluation techniques for self-healing efficiency. Araujo et al extruded microscale poly(methyl methacrylate) capsules with the width less than a millimeter using a single screw extruder (Araujo et al, 2018). The authors encapsulated an accelerating agent inside those PMMA capsules and backtracked the number of capsules broken during the mixing process by quantifying the accelerating effect observed during the setting process.…”
Section: Capsule-based Approachmentioning
confidence: 99%
“…Araujo et al [27] carried out real-scale tests on concrete beams of 2.5 m x 0.40 m x 0.20 m reinforced with four ribbed steel bars (Ø=10 mm). Poly(methyl methacrylate) and glass capsules were used to encapsulate the healing agent.…”
Section: Chloride Ingress In Real-scale Specimensmentioning
confidence: 99%